Given the following expression;
![\sin 115\cos 35+\cos 115\sin 35](https://img.qammunity.org/2023/formulas/mathematics/college/uniqlrg8c2eu0n5oea5rzc1oc3ntu7kufo.png)
We begin by using the following trig identity;
![\cos A\sin B+\cos B\sin A=\sin (A+B)](https://img.qammunity.org/2023/formulas/mathematics/college/3dfajdm3tll8l2dtyefczontuuzhawnoks.png)
Using the values of the angles given, we have;
![\begin{gathered} \sin 115\cos 35+\cos 115\sin 35=\sin (115+35) \\ =\sin 150 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hxa857kt5aq7500ifjfge4p18e1dfrkyzu.png)
We can now rewrite as follows;
![\sin 150=\sin (60+90)](https://img.qammunity.org/2023/formulas/mathematics/college/aluwqq4d3fkydv7wl2dhu1isnh86pwnbxa.png)
We can now apply the summation identity as identified earlier and we'll have;
![\sin (60+90)=\sin 60\cos 90+\cos 60\sin 90](https://img.qammunity.org/2023/formulas/mathematics/college/thw3qbbf8jqcaeiefeb6s1bq3ansifbv0v.png)
At this point we can apply the values of special angles, as shown;
![\begin{gathered} \sin 60=\frac{\sqrt[]{3}}{2},\cos 60=(1)/(2) \\ \sin 90=1,\cos 90=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/475gi4atqvsux8ntqduwe3tv4u1cepjo2z.png)
Substitute these and we now have;
![\begin{gathered} \sin (60+90)=(\frac{\sqrt[]{3}}{2}*0)+((1)/(2)*1) \\ \sin (60+90)=0+(1)/(2) \\ \sin (60+90)=(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9jxrltse25d36j83boknuqob14u36brz1u.png)
ANSWER;
The exact value of the given expression is
![(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/geika1bebdh49vlmy8m866aot9b5u0n47d.png)